Non-occupational falls from ladders in men 50 years and over: Contributing factors and impact. Issue 8 (August 2020) - Schaffarczyk, Katherine; Nathan, Sally; Marjadi, Brahmaputra; Hsu, Jeremy; Poulos, Roslyn
Highlights: ISS designation of minor trauma did not adequately reflect ongoing functional limitations four or more months post fall. Predisposing factors are multifactorial (individual and interpersonal) reflecting generational and community values. The most salient pre-fall factor was a lack of assessment of risk, reflecting individual and community factors. There was considerable impact with respect to quality of life, mental wellbeing and the longer-term impacts across multiple life domains. The impacts of falls are life changing to not just the men, but their families, and at a broader level, the health care system. Severe injury occurred even with falls from a low height. A collaborative, innovative approach involving key stakeholders is required to consider, prioritise and implement effective interventions. Abstract: Background: Research into falls from ladders in older men in the non-occupational setting is limited, yet such falls are increasing. Aim: To explore non-occupational falls from ladders in older men presenting to a major trauma centre; identify factors influencing ladder climbing behaviour and explore the post fall impacts. Methods: We conducted a retrospective review of medical records of men aged 50 years and older admitted to a major trauma centre following a non-occupational ladder fall between February 2011 and December 2013. Interviews were conducted with a sample of men (and their partners where possible) after discharge from hospital. The Late Life Functional Disability Instrument-computer adaptive testing (LLFDI-CAT) was administered to determine pre-and post-fall function. Basic descriptive analysis was undertaken on medical record data. Thematic analysis was used with the socioecological (SE) model as an interpretive frame. Results: Of 86 men included in the study (range 50–85 years, mean age 64.7 years), 27% sustained severe trauma. The median length of stay was 4 days. Fourteen interviews were conducted with 19 participants (12 men, 7 spouses). The most salient pre-fall factor was a lack of assessment of risk, reflecting individual and community factors. Post fall impacts were identified in all domains of the SE model. A statistically significant decrease in self-reported post-fall compared with pre-fall LLFDI-CAT scores for interviewed men was found, despite seven having minor trauma (Injury Severity Score [ISS]<12) on admission. Conclusion: Ladder fall injuries cause marked morbidity, often with life changing impacts, even with minor trauma. Contributing factors are multifactorial. Injury prevention strategies should address these factors.